The role of root hairs in water uptake: recent advances and future perspectives - Cai, Gaochao; Ahmed, Mutez Ali (Journal of experimental botany, 2022)
Sufficient water is essential for plant growth and production. Root hairs connect roots to the soil, extend the effective root radius, and greatly enlarge the absorbing surface area. Although the efficacy of root hairs in nutrient uptake, especially phosphorus, has been well recognized, their role in water uptake remains contentious. Here we review recent advances in this field, discuss the factors affecting the role of root hairs in water uptake, and propose future directions. We argue that root hair length and shrinkage, in response to soil drying, explain the apparently contradictory evidence currently available. Our analysis revealed that shorter and vulnerable root hairs (i.e. rice and maize) made little, if any, contribution to root water uptake. In contrast, relatively longer root hairs (i.e. barley) had a clear influence on root water uptake, transpiration, and hence plant response to soil drying. We conclude that the role of root hairs in water uptake is species (and probably soil) specific. We propose that a holistic understanding of the efficacy of root hairs in water uptake will require detailed studies of root hair length, turnover, and shrinkage in different species and contrasting soil textures.